PROTOTYPE DESIGN OF BATTERY CHARGING SYSTEM WITH THE USE OF REPEATED WATER CYCLE AT PICOHIDRO POWER PLANT - MARIANUS CHRISTOSANTO NOFU; Frans Likadja; Almido Ginting (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
Picohydro power plant (PLTPH) is the smallest scale hydroelectric power plant with a capacity of less than 5 kW. Still like other hydropower plants, PLTPH applications are also often constrained by changes in water discharge due to the dry season. This research is here to design and test a prototype battery charging system with repeated water cycles on PLTPH consisting of several components such as water pumps, pelton turbines, DC generators, Smart Valves and relay time to control the charging system and also the battery as an energy store. The research method used is an experimental method, where the focus of the test is the output of the generator at a certain height and discharge and then compared to the discharge of water that is pumped back to be reused. As a result, the output of the generator was obtained at a height of 3.9m, namely 1.7V and 2.4A, which is low enough to be used in charging the battery, so a step up module is needed to increase the generator output voltage. Testing was also carried out to see how the Solar Panels handled the load at the beginning of the system. This system is still not efficient in charging time, but it is quite integrated both in analysis and concept so that it can be developed, of course, with more mature consideration and concepts